Chronicle of Zodchestvo in Siberia 23 - Grigoryeva, Elena (project baikal, 2023)
From 14-17 June the XXIII interregional architectural festival “Zodchestvo in Siberia 2023” took place in Irkutsk. The article presents the chronicle of “Zodchestvo in Siberia 2023”, the geography of participants, the list of speakers, the stars of Russian architecture, invited to give master-classes, as well as the themes of excursions.